2020
DOI: 10.1002/term.3025
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal substrates alter the migratory responses of nonmyelinating Schwann cells to controlled brain‐derived neurotrophic factor gradients

Abstract: Neurodegeneration and dysfunction cause mobility impairment and/or paralysis in millions of adults, worldwide. Motor deficit and recovery in adults depend upon the plasticity of the neuromuscular junction (NMJ), a tripartite, biochemical synapse that transduces electrical impulses from the brain into voluntary contraction of skeletal muscle. Nonmyelinating Schwann cells (nmSCs) of the NMJ have been increasingly recognized as active synaptic partners with motor neurons and muscle and have become recent therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…EBS is most clinically used as a diluent of therapeutics for disorders of the meninges, which partially contain CSF and have been implicated in neuromuscular disease, neurodegenerative disorders, and some forms of cancer (Oka, Yamamoto, Nonaka, & Tomonaga, 1996; Shestakova, Healey, Zhao, Rezk, & Nakagiri, 2019). Results of our study illustrate that EBS solutions facilitate ShC survival, morphology, and proliferation similar to those measured in traditional DMEM medium, and additionally support glial chemotactic behaviors in response to the regenerative agent, brain‐derived growth factor (BDNF) (Singh, Robles, & Vazquez, 2020). Moreover, SCE cultured with EBS solutions exhibited survival rates comparable to those within conventional NB medium, and demonstrated rates of cellular outgrowth commensurate with reported in vivo measurements.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…EBS is most clinically used as a diluent of therapeutics for disorders of the meninges, which partially contain CSF and have been implicated in neuromuscular disease, neurodegenerative disorders, and some forms of cancer (Oka, Yamamoto, Nonaka, & Tomonaga, 1996; Shestakova, Healey, Zhao, Rezk, & Nakagiri, 2019). Results of our study illustrate that EBS solutions facilitate ShC survival, morphology, and proliferation similar to those measured in traditional DMEM medium, and additionally support glial chemotactic behaviors in response to the regenerative agent, brain‐derived growth factor (BDNF) (Singh, Robles, & Vazquez, 2020). Moreover, SCE cultured with EBS solutions exhibited survival rates comparable to those within conventional NB medium, and demonstrated rates of cellular outgrowth commensurate with reported in vivo measurements.…”
Section: Introductionsupporting
confidence: 63%
“…Subsequent experiments used EBS as a diluent fluid within the bridged gLL device to produce chemoattractive gradient fields of extracellular BDNF (Figure 5). Previous work from our lab and others have shown that ShC migratory responses to BDNF are important to glia‐ and NMJ‐targeted NS therapies (Singh et al., 2020). The data here illustrate that ShC responded chemotactically to BDNF stimuli generated within DMEM or EBS solutions with high similarity.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A 20-mL volume of polydimethylsiloxane (PDMS, Dow Corning, Midland, MI) was then poured onto the final patterned wafer surface and oven cured (300 • C, 15 min) to produce an elastomer of 2-3 mm in thickness. Lastly, oxygen plasma was applied to the inner surfaces of the PDMS elastomer and a piranha-cleaned glass microscope slide using a 30-s corona treatment (Electro-technic Products Inc., Chicago, IL, USA) [49,50,58] before press fitting to create the closed µOS system, as done previously by our lab [59,60] ( Figure 3F). The μOS is manufactured using a two-step photolithography process with elastomeric micromolding.…”
Section: System Fabricationmentioning
confidence: 99%